2017
DOI: 10.17706/ijeeee.2017.7.4.272-279
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of the Patient Safety Culture Based on the Safety Attitudes Questionnaire in a State-Owned Regional Hospital in Taiwan

Abstract: The patient safety culture based on the safety attitudes questionnaire from a state-owned regional teaching hospital in Taiwan is analyzed in terms of six dimensions by independent sample t test and one-way analysis of variance from the viewpoints of physicians and nurses. Gender, age, job position, job status, and education are critical demographic variables that have significant impacts on five out of six dimensions. In contrast, teamwork climate, safety climate, job satisfaction, and perceptions of manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Safety attitudes questionnaire developed by Sexton et al [3] is the most commonly used questionnaire worldwide to assess the patient safety culture in healthcare organizations from employees' viewpoints [2], [11]. Safety attitudes questionnaire contains thirty questions, which can be categorized into six dimensions, including teamwork climate, safety climate, perceptions of management, job satisfaction, stress recognition, and working conditions [11], [12]. The detailed information is summarized in Table I.…”
Section: Safety Attitudes Questionnairementioning
confidence: 99%
“…Safety attitudes questionnaire developed by Sexton et al [3] is the most commonly used questionnaire worldwide to assess the patient safety culture in healthcare organizations from employees' viewpoints [2], [11]. Safety attitudes questionnaire contains thirty questions, which can be categorized into six dimensions, including teamwork climate, safety climate, perceptions of management, job satisfaction, stress recognition, and working conditions [11], [12]. The detailed information is summarized in Table I.…”
Section: Safety Attitudes Questionnairementioning
confidence: 99%
“…Safety attitudes questionnaire developed by Sexton et al [3] having six dimensions along with 30 questions has been widely used to survey the medical staffs' perceptions of patient safety culture in healthcare organizations worldwide [12], [13]. Six dimensions are teamwork climate, safety climate, perceptions of management, job satisfaction, stress recognition, and working conditions [12], [13]. The detailed information along with brief definitions of dimensions are provided in Table I.…”
Section: Safety Attitudes Questionnairementioning
confidence: 99%
“…Furthermore, Hamdan proposed that gender and age are critical factors impacting patient safety [31]. Wu et al reported that gender, age, job position, job status, and education are critical factors influencing the patient safety culture [32]. Lee et al believed that medical staff with different demographic variables might have different perceptions on patient safety culture and using a longitudinal study to assess patient safety culture enables hospital management to trace the performance and trends on a timely basis [33].…”
Section: Introductionmentioning
confidence: 99%